A Hybrid Enhancement Artificial Bee Colony Algorithm for High-efficiency Service Selection - ZHANG Hong-guo; CHEN Yang; MA Chao; FANG Zhou; HUANG Hai (Journal of Harbin University of Science and Technology)
In order to implement service selection efficiently，and to build a complex software service system that can meet the needs of users by using service aggregation method，this paper proposes a Hybrid Enhancement Artificial Bee Colony ( HEABC) algorithm. The algorithm combines K-means algorithm，K-Nearest Neighbor ( KNN) algorithm and ABC algorithm to ensure that ABC algorithm always maintains continuity when updating solutions in discrete solution space. The algorithm enhances the exploration and development capabilities of the bee colony by increasing the ability of information sharing between bee colonies. In terms of non-functional perception of software services，this paper introduces the concept of service contract to achieve more comprehensive user satisfaction and dynamic needs. The simulation experiment used 60 different sets of data and compared it to other algorithms in terms of quality and execution time. The results show that compared with other algorithms，this algorithm has improved the solution time and the solution quality.